On Hadamard composition of Gelfond-Leont'ev derivatives of entire and analytic functions in the unit disk - Mulyava, O.M.; Sheremeta, M.M. (Carpathian Mathematical Publications, 2021)
For an entire function and an analytic in the unit disk function the growth of the Hadamard composition of their Gelfond-Leont'ev derivatives is investigated in terms of generalized orders. A relationship between the behaviors of the maximal terms of Hadamard composition of Gelfond-Leont'ev derivatives and of the Gelfond-Leont'ev derivative of Hadamard composition is established.